2012
DOI: 10.2337/dc11-1583
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Superficial Subcutaneous Fat

Abstract: OBJECTIVEUnlike visceral adipose tissue (VAT), the association between subcutaneous adipose tissue (SAT) and obesity-related morbidity is controversial. In patients with type 2 diabetes, we assessed whether this variability can be explained by a putative favorable, distinct association between abdominal superficial SAT (SSAT) (absolute amount or its proportion) and cardiometabolic parameters.RESEARCH DESIGN AND METHODSWe performed abdominal magnetic resonance imaging (MRI) in 73 patients with diabetes (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 28 publications
5
89
0
3
Order By: Relevance
“…Previous studies have shown that subcutaneous abdominal fat is related to a lower risk for type 2 diabetes and that fasting glucose levels are lower in diabetic patients with higher subcutaneous abdominal fat levels. 52,53 It is possible that subcutaneous fat may protect against MetS by acting as a reservoir for systemic triglycerides, 54 thus preventing their deposition in visceral adipose tissue, skeletal muscle or liver, which then attenuates insulin resistance. The positive association of trunk FFSTM with MetS was a novel finding, and was due to the negative association of FFSTM with HDL levels, as has been observed in two previous studies.…”
Section: Metabolic and Anthropometric Factorsmentioning
confidence: 99%
“…Previous studies have shown that subcutaneous abdominal fat is related to a lower risk for type 2 diabetes and that fasting glucose levels are lower in diabetic patients with higher subcutaneous abdominal fat levels. 52,53 It is possible that subcutaneous fat may protect against MetS by acting as a reservoir for systemic triglycerides, 54 thus preventing their deposition in visceral adipose tissue, skeletal muscle or liver, which then attenuates insulin resistance. The positive association of trunk FFSTM with MetS was a novel finding, and was due to the negative association of FFSTM with HDL levels, as has been observed in two previous studies.…”
Section: Metabolic and Anthropometric Factorsmentioning
confidence: 99%
“…Internal abdominal AT is associated with higher metabolic risk (9), whereas abdominal or nonabdominal superficial subcutaneous AT may be protective (10). Indirect body composition techniques require assumptions to enable the calculation of fat mass, and although they may provide an indication of fat mass distribution, they are unable to differentiate individual AT compartments.…”
mentioning
confidence: 99%
“…El exceso de grasa visceral puede ser un marcador de disfuncionalidad del tejido adiposo, el cual no es capaz de almacenar adecuadamente el exceso calórico y que determina la susceptibilidad para desarrollar síndrome metabólico. Varios estudios sugieren que cuando el exceso calórico puede ser depositado en forma de tejido adiposo subcutáneo sensible a la insulina (capaz de expandirse mediante hiperplasia), el individuo estará protegido contra el desarrollo de síndrome metabólico [44][45][46][47] . No obstante, en casos en los cuales el tejido adiposo está ausente, deficiente o es resistente a la insulina y tiene una capacidad limitada para almacenar el exceso de energía (tejido adiposo hipertrófico), el exceso de triglicéridos será depositado en lugares indeseables como hígado, corazón, músculo esquelético y en el tejido adiposo visceral, fenómeno conocido como depósito de grasa ectópica 48,49 .…”
Section: Discussionunclassified
“…En la anterior línea de razonamiento, puede postularse que en nuestra muestra de estudio el hecho de que el pliegue abdominal como indicador de grasa subcutánea, se relacione positivamente con el tono vagal y negativamente con el tono simpático sugiere que en hombres jóvenes, delgados y físicamente activos, la posibilidad de acumular el exceso calórico en forma de tejido adiposo subcutáneo (sensible a la insulina) puede ser un mecanismo de protección contra el depósito de grasa intra-abdominal, el desarrollo de síndrome metabólico y se asocia a un adecuado balance autonómico 47 (Figura 1). Por el contrario, con el aumento de la edad, un estilo de vida sedentario o el abandono de un estilo físicamente activo y la ganancia excesiva de peso, se desarrollaría resistencia a la insulina, que entre muchas otras, conduce a disfuncionalidad del tejido adiposo, el cual con una capacidad limitada para depositar el exceso calórico a nivel subcutáneo, empieza a depositarse de manera ectópica a nivel visceral contribuyendo al desarrollo de síndrome metabólico (independientemente de la grasa corporal total y subcutánea) [41][42][43] y se asocia a desregulación autonómica con predominio simpático 53 .…”
Section: Discussionunclassified